Sustained decline in birth weight and increased rate of preterm infants born small for gestational age in Japan - Akinori Moriichi; Erika Kuwahara; Narumi Kato (Frontiers Media S.A., 2024)
BackgroundBirth weights have continued to decline in Japan in recent years. However, secular trend changes such as the birth weight relative to the week of gestation remain to be explored. This study aimed to determine the trends over time in mean birth weight and small for gestational age (SGA) rate for each gestational week.MethodsWe used a large dataset of 27,015,792 births obtained from birth certificates between 1997 and 2021. Births from 22 to 41 weeks of gestation were evaluated in six groups (22-24, 25-27, 28-31, 32-33, 34-36, and 37-41 weeks of gestational age). For each group, secular trend changes in the z-scores calculated from standard birth weight values were assessed. Time trends in the proportion of SGA and mean birth weight z-scores were evaluated using the Cochran-Armitage trend test and linear regression analysis. Binomial logistic regression was performed to ascertain the effects of gestational age, sex, primiparity, number of births, and maternal age on the likelihood of SGA.ResultsThe mean birth weight of preterm infants continued to decrease, and the z-score for mean birth weight decreased linearly, falling to −0.7 at 25-27 weeks of gestation from 1997-2001 (first period) to 2017-2021 (final period). Maternal age continued to increase from the first period to the last period for all weeks of gestation. There was a linear increase in the SGA rate in preterm infants born at <34 weeks. Odds ratios for the likelihood of SGA were 1.3 times higher for maternal age ≥40 years than that for 25-29 years (95% CI: 1.29-1.33, p < 0.001).ConclusionsIn Japan, there has been a continuous decline in birth weight and an increase in the rate of preterm SGA infants.